Islamic Education Based on Literacy Tradition in Educating the People of Islamic Union (PERSIS) - Agus Susilo Saefullah; Ila Nurlaila Hidayat (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Islamic Education Based on Literacy Tradition in Educating the People of Islamic Union (PERSIS)Objective: This study aims to examine the literacy tradition in public education developed by the Islamic Association (PERSIS) using a literature review and historical analysis. Methods: This research was conducted in 2023. The research uses the heuristic method to collect data, and data analysis uses historical analysis of the development of PERSIS in literacy and education. Results: PERSIS has successfully developed a strong literacy tradition since its establishment, which focuses on spreading and understanding Islamic teachings by the spirit of returning to the Qur'an and As-Sunnah. Conclusion: PERSIS books and publications have become a major means of enriching Islamic literature in Indonesia and helping to deepen people's understanding of Islamic teachings. They have positively impacted the internal PERSIS community and contributed to developing public education in Indonesia. Contribution: The results of this study contribute to strengthening PERSIS' literacy-based proselytization strategy, both in print and digital media, so that the wider community can more easily access Islamic teachings.INDONESIAN: Pendidikan Islam Berbasis Tradisi Literasi dalam Mencerdaskan Umat Persatuan Islam (PERSIS)Tujuan: Penelitian ini bertujuan untuk mengkaji tradisi literasi dalam pendidikan masyarakat yang dikembangkan oleh Persatuan Islam (PERSIS) menggunakan tinjauan literatur dan analisis sejarah. Metode: Penelitian ini dilaksanakan pada tahun 2023 menggunakan metode heuristik untuk mengumpulkan data. Sejarah perkembangan PERSIS dalam bidang literasi dan pendidikan dianalisis. Hasil: PERSIS berhasil mengembangkan tradisi literasi yang kuat sejak berdiri. Tradisi literasi PERSIS berfokus pada penyebaran dan pemahaman ajaran Islam sesuai dengan semangat untuk kembali kepada Al-Qur’an dan As-Sunah. Kesimpulan: Buku dan penerbitan PERSIS menjadi sarana utama dalam memperkaya literatur Islam di Indonesia dan memperdalam pemahaman masyarakat terhadap ajaran Islam. Hal ini berdampak positif pada komunitas internal PERSIS dan juga berkontribusi penting bagi perkembangan pendidikan masyarakat di Indonesia. Kontribusi: Penelitian ini berkontribusi dalam memperkuat strategi dakwah PERSIS yang berbasis literasi di media cetak maupun digital sehingga masyarakat luas dapat lebih mudah mengakses ajaran Islam.